Initiation into the mysteries of the ancient world - Bremmer, Jan N. (Münchner Vorlesungen zu antiken Welten, 2014)
This book explores ancient mystery cults and their influence on emerging Christianity. The author discusses the famous Eleusian Mysteries as well as smaller and lesser-known Greek and Roman mysteries, offering an indispensable in-depth analysis of this fascinating phenomenon.